2022
DOI: 10.1155/2022/3888798
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA KIF9-AS1 Accelerates Hepatocellular Carcinoma Growth by Recruiting DNMT1 to Promote RAI2 DNA Methylation

Abstract: Background. Hepatocellular carcinoma (HCC) is a very common malignant tumor. Long noncoding RNAs (lncRNAs) enable discoveries of new therapeutic tumor targets. We aimed to study the role and potential regulatory mechanisms of the lncRNA KIF9-AS1 in HCC. Methods. CCK-8, scratch assay, and flow cytometry were used to detect cell proliferation, migration, and apoptosis, respectively. Bax, Bcl-2, ERK, and pERK expression were measured by western blotting. StarBase predicted KIF9-AS1 expression in HCC and paracance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…96 Furthermore, RNAs can affect gene methylation or directly impact HCC by acting on the methylation level of the corresponding gene. [97][98][99][100] RNA methyltransferases (METTs) and RNA-binding proteins (RBPs) offer promising therapeutic targets in HCC. In m6A, METTL3 depends on the YTH domain family 2 (YTHDF2) of RBPs to regulate the proliferation, migration, and invasion of HCC cells.…”
Section: Role Of Rna Associated Methylation In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…96 Furthermore, RNAs can affect gene methylation or directly impact HCC by acting on the methylation level of the corresponding gene. [97][98][99][100] RNA methyltransferases (METTs) and RNA-binding proteins (RBPs) offer promising therapeutic targets in HCC. In m6A, METTL3 depends on the YTH domain family 2 (YTHDF2) of RBPs to regulate the proliferation, migration, and invasion of HCC cells.…”
Section: Role Of Rna Associated Methylation In Hccmentioning
confidence: 99%
“… 118 The formation of M1A is catalyzed by methyltransferases, with these “writers” specifically recognizing m1A sites as well as inducing downstream effects. 97 Genetic variations in m1A regulators may be linked to mutations in oncogenes, playing a role in the carcinogenesis or metabolic reprogramming of HCC. 90 While M1A regulates the PI3K/AKT/mTOR pathway in gastrointestinal cancers, its specific mechanisms in HCC remain to be fully elucidated.…”
Section: Role Of Rna Associated Methylation In Hccmentioning
confidence: 99%
“…Abnormal expression of lncRNA KIF9-AS1 has been reported in a variety of tumor cells and is closely associated with the progression of nasopharyngeal carcinoma ( You et al, 2020 ), hepatocellular carcinoma ( Yu et al, 2022 ), and ovarian cancer ( Li and Zhan, 2020 ). In Jin et al ’ s study, KIF9-AS1 was found to be highly expressed in renal cell carcinoma (RCC) tissue cells.…”
Section: Introductionmentioning
confidence: 99%